MR imaging of aortic coarctation - Bešlić, Šerif (Radiology and oncology (Ljubljana), 2004)
Purpose. The purpose of this paper is to analyse the contribution of MRI as diagnostic procedure in the preoperative diagnosis of aortic coarctation (CoA), in patients with clinical and echocardiographic suspicion for this disease. Patients and methods. During the period of three years, eight patients were examined, 5 (62.5%) male and 3 (37.5%) female patients with clinical echocardiographic suspicion of CoA. The ratio between male and femalepatients was 1.7 : 1. The youngest patient was 3 and the oldest 46 years(median age was 15 years). Without administration of contrast media and using body coil the examinations were performed with MR machine Magnetom 1.0 Tesla ( Siemens ), with the slice thickness of 6 mm, Fast spin-echo (FSE) T1W sequencas, Cine gradient echo (GRE) sequence with slab 7 mm and time of flight(TOF) sequence with MIP reconstructions were applied. During the examinations the patients underwent also ECG gating. Examinations were done inaxial, coronal and obligue sagittal projections with measuring of the dimensions of cardiovascular structures. Results. CoA was found in 8 (100%) patients. In 7 (87.5%) cases, coarctation developed at isthmus and in one case, coarctation was detected at the horizontal part of aortic arch, between the truncus arteriosus of the left carotid communis artery. Aortal insufficiency was found in 7 (87.5%) patients; in four of them (50%), bicuspidia was confirmed (bicuspid aortic valve), 7 (87.5%) patients had slightly expressed hypertrophy of the left ventricle. Two (25%) patients had dilatation of the ascendant aorta, six (75%) wider outgoing vessels of the aortic arch, four (50%) had well developed arterial collaterals and 2 (25%) patients rib notching. In 2 (25%) patients as side finding thymus persistent was found. Average diameter of coarctation was 10 mm. (Abstract truncated at 2000 characters).
Keywords: aorta; Aorta, zožitev; Aortic Coarctation; Diagnosis; diagnostika; Echocardiography; Ehokardiografija; jedrska magnetna resonanca; Magnetic Resonance Imaging; Magnetna resonanca slikovna; ožilje; zožitev